Comparative study of monolithic and precast concrete beam-to-column connections - Abd. Rahman, Ahmad Baharuddin; Ghazali, Abdul Rahim; Abd. Hamid, Zuhairi (Construction Industry Research Institute of Malaysia (CREAM), 2008)
This paper presents a new technique for predicting noise from construction site using probabilistic approach. The advantage of the method is its ability to predict a set of noise levels during a working day period weighted by their probabilities of cumulative distribution or temporal distribution. This method has introduced different degree of noises according to different indices such as L10, L50 and L90. The indices could be used to avoid the annoyance due to construction activities and the complaints from nearby residents during construction activities. The temporal distribution of the model could be applied to predict the equivalent continuous sound level (LAeq) experienced over a short period as commonly practiced by the local authority staff when checking for conformance with a specified level during the construction process. The method could be used as the basis of an operational management tool for noise abatement scheme towards maintaining a more sustainable environment